Virtual Field Trip to the Youth Pledge Museum in History Learning at SMA Negeri 7 Banjarmasin: Karyawisata Virtual Museum Sumpah Pemuda dalam Pembelajaran Sejarah di SMA Negeri 7 Banjarmasin - Muhammad Firnanda; Susanto, Heri; Abbas, Ersis Warmansyah; Sriwati, Sriwati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The Ministry of Education and Culture, through the Museum Sumpah Pemuda's implementing unit, has introduced virtual visitation services. Virtual visits, or virtual field trips, in history education serve as an alternative to real field trips. This research aims to describe the implementation of history education using virtual field trips to the Museum Sumpah Pemuda in SMA Negeri 7 Banjarmasin, specifically focusing on the topic of Sumpah Pemuda, conducted in the year 2021. The research utilized a descriptive qualitative research method, involving observation, interviews, and document analysis. The virtual field trip was designed as part of the history education curriculum, encompassing planning, implementation, and evaluation phases. The implementation of the learning process consisted of an opening phase, core activities, and a closing phase. The utilization of virtual field trips in history education at SMA Negeri 7 Banjarmasin is expected to be an efficient alternative that enhances students' learning experiences.